Antibacterial titanium nano-patterned arrays inspired by dragonfly wings - Bhadra, Chris M.; Khanh Truong, Vi; Pham, Vy T. H.; Al Kobaisi, Mohammad; Seniutinas, Gediminas; Wang, James Y.; Juodkazis, Saulius; Crawford, Russell J.; Ivanova, Elena P. (Scientific reports, 2015)
Titanium and its alloys remain the most popular choice as a medical implant material because of its desirable properties. The successful osseointegration of titanium implants is, however, adversely affected by the presence of bacterial biofilms that can form on the surface and hence methods for preventing the formation of surface biofilms have been the subject of intensive research over the past few years. In this study, we report the response of bacteria and primary human fibroblasts to the antibacterial nanoarrays fabricated on titanium surfaces using a simple hydrothermal etching process. These fabricated titanium surfaces were shown to possess selective bactericidal activity, eliminating almost 50% of Pseudomonas aeruginosa cells and about 20% of the Staphylococcus aureus cells coming into contact with the surface. These nano-patterned surfaces were also shown to enhance the aligned attachment behavior and proliferation of primary human fibroblasts over 10 days of growth. These antibacterial surfaces, which are capable of exhibiting differential responses to bacterial and eukaryotic cells, represent surfaces that have excellent prospects for biomedical applications.